Ethical attitudes and perspectives of AI use in medicine between Croatian and Slovenian faculty members of school of medicine: Cross-sectional study. - Štefan Grosek; Stjepan Štivić; Ana Borovečki; Marko Ćurković; Jaro Lajovic; Ana Marušić; Antonija Mijatović; Mirjana Miksić; Suzana Mimica; Eva Škrlep; Kristina Lah Tomulić; Vanja Erčulj (PLoS ONE)
Background Artificial intelligence (AI) is present in preclinical, clinical and research work, in various branches of medicine. Researchers and teachers at school of medicines may have different ethical attitudes and perspectives about the implementation of AI systems in medicine. Methods We conducted an online survey among researchers and teachers (RTs) at the departments and institutes of two Slovenian and four Croatian Schools of Medicine. Results The sample included 165 and 214 researchers and teachers in Slovenia and Croatia, respectively. The sample of respondents in Slovenia and Croatia was comparable in demographical characteristics. All participants reported high emphasis on the bioethical principles when using artificial intelligence in medicine, its usefulness in certain circumstances, but also caution regarding companies providing AI systems and tools. Slovenian and Croatian researchers and teachers shared three similar perspectives on the use of AI in medicine-complying with highest ethical principles, explainability and transparency and usefulness of AI tools. Higher caution towards use of AI in medicine and effect on autonomy of physicians was expressed in Croatia, while in Slovenia high emphasis was put on understanding how AI works, but also the concerns regarding willingness and time of physicians to learn about AI. Conclusion Slovenian and Croatian researchers and teachers share ethical attitudes and perspectives with international researchers and physicians. It is important to facilitate understanding of the implications of AI use in medicine and set a solid evidence-based ground to tackle ethical and legal issues.